2005
DOI: 10.1080/14622200412331328538
|View full text |Cite
|
Sign up to set email alerts
|

A sensitization–homeostasis model of nicotine craving, withdrawal, and tolerance: Integrating the clinical and basic science literature

Abstract: Recent reports suggest that nicotine withdrawal symptoms are common among adolescents after a few weeks of intermittent tobacco use. No current model of nicotine dependence had predicted the rapid development of symptoms of dependence and withdrawal before the development of tolerance. We present a model that integrates neuroscience with clinical observations regarding how nicotine dependence develops, progresses, and resolves in humans. The central tenet of this sensitization-homeostasis model is that nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
124
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 119 publications
(171 reference statements)
12
124
0
4
Order By: Relevance
“…These animals are therefore in the same state of 5HT and AC function as would be expected in the adolescent during withdrawal after nicotine administration. Interestingly, this interpretation is in keeping with a recent hypothesis of the origin of nicotine dependence, the 'sensitization-homeostasis theory' (DiFranza and Wellman, 2005), which postulates that the stimulatory and inhibitory adjustments to nicotine administration produce reversible as well as permanent changes in activity of specific neuronal circuits. The fact that alterations in 5HT synaptic signaling emerge upon discontinuation of adolescent nicotine administration, and that prenatal nicotine exposure alters the pattern of such reactivity, are all in keeping with this model, and similarly suggest that persistent changes will leave prenatally exposed individuals vulnerable to relapse upon cessation of adolescent smoking (DiFranza and Wellman, 2005).…”
Section: Effects Of Prenatal Nicotine Exposure On the Response To Nicsupporting
confidence: 52%
See 1 more Smart Citation
“…These animals are therefore in the same state of 5HT and AC function as would be expected in the adolescent during withdrawal after nicotine administration. Interestingly, this interpretation is in keeping with a recent hypothesis of the origin of nicotine dependence, the 'sensitization-homeostasis theory' (DiFranza and Wellman, 2005), which postulates that the stimulatory and inhibitory adjustments to nicotine administration produce reversible as well as permanent changes in activity of specific neuronal circuits. The fact that alterations in 5HT synaptic signaling emerge upon discontinuation of adolescent nicotine administration, and that prenatal nicotine exposure alters the pattern of such reactivity, are all in keeping with this model, and similarly suggest that persistent changes will leave prenatally exposed individuals vulnerable to relapse upon cessation of adolescent smoking (DiFranza and Wellman, 2005).…”
Section: Effects Of Prenatal Nicotine Exposure On the Response To Nicsupporting
confidence: 52%
“…Interestingly, this interpretation is in keeping with a recent hypothesis of the origin of nicotine dependence, the 'sensitization-homeostasis theory' (DiFranza and Wellman, 2005), which postulates that the stimulatory and inhibitory adjustments to nicotine administration produce reversible as well as permanent changes in activity of specific neuronal circuits. The fact that alterations in 5HT synaptic signaling emerge upon discontinuation of adolescent nicotine administration, and that prenatal nicotine exposure alters the pattern of such reactivity, are all in keeping with this model, and similarly suggest that persistent changes will leave prenatally exposed individuals vulnerable to relapse upon cessation of adolescent smoking (DiFranza and Wellman, 2005). Indeed, studies in adolescent smokers show emergence of both cognitive impairment and depression upon smoking cessation, contributing to the failure to quit (Colby et al, 2000;Goodman and Capitman, 2000;Hurt et al, 2000;Martini et al, 2002;Patten et al, 2000;Salin-Pascual et al, 1995;Tsoh et al, 2000;Wu and Anthony, 1999).…”
Section: Effects Of Prenatal Nicotine Exposure On the Response To Nicsupporting
confidence: 52%
“…Based on the Sensitization-Homeostasis model (DiFranza and Wellman, 2005), nicotine exposure through SHS could prime the addiction pathway and lead to experiencing ND symptoms (Bélanger et al, 2008). Recent findings support this notion of pharmacological priming.…”
Section: Discussionmentioning
confidence: 54%
“…These brain regions comprise key structures within the brain reward system, which extends from the dopaminergic neurons in the ventral tegmental area to the ventral striatum (nucleus accumbens), with projections to the orbitofrontal, anterior cingulate, and prefrontal cortices (Balfour et al, 2000;Di Chiara, 2000;Grillner and Svensson, 2000;Mameli-Engvall et al, 2006). It has been hypothesized that nicotine, like other psychostimulants, sensitizes the reward system, engendering craving (Robinson and Berridge, 2003;DiFranza and Wellman, 2005). In studies of cigarette craving, Brody et al (2002Brody et al ( , 2004 found that an increase in the metabolic activity of the orbitofrontal cortex was positively correlated with craving for cigarettes.…”
Section: Discussionmentioning
confidence: 99%